Abdominal Burkitt’s lymphoma in Children - Ghoroubi, Javad; Mirshemirani, Alireza; Kouranloo, Jafar; Nazari, Shiva (Iranian Journal of Pediatric Surgery, 2015)
Background: Burkitt’s lymphoma is a high grade B-cell neoplasm, which is a kind of small non-cleaved cell lymphoma. It is presumably the fastest growing human malignancy, and the patients are prone to develop tumor-lysis syndrome. Here we present findings on our patients with Burkitt lymphoma. Materials and Methods: This descriptive retrospective study included 46 children with abdominal Burkitt's lymphoma who were treated during 15 years from June 1998 to Dec 2013 at Mofid Children’s Hospital. Results: Offourty six patients 32 (70%) were boys and 14 (30%) were girls with ages ranging from 2 to 14 years. Surgical exploration was carried out in all cases, the lesions were located in the small intestine (N=17), large intestine (N=15), ileocecal region (N=12), and stomach (N=2). We performed a complete mass resection in 16 cases, debulking in 10 and lymph node/mass biopsy in 20 cases. Pathologic examination revealed Burkitt’s lymphoma for all patients. The majority were stageIIE and stage IIIE (24 and 19 respectively). Post-operative complications were seen in five cases with the most common being persistent ileus. All patients received a sort of systemic chemotherapy. The mean follow up duration was 6 years. Death occurred in 7(15%) of our patients, due to tumor lysis syndrome and acute renal failure. Conclusion: The extent ofdisease at presentation is the most important prognostic factor in abdominal Burkitt’s lymphoma. Children with BL are at a high risk of tumor lysis syndrome before or during chemotherapy. Surgery still plays an important role in this pathology, and chemotherapy offers an excellent chance for long term disease free survival.